Synthesis and application of mesoporous molecular sieve for miniaturized matrix solid‐phase dispersion extraction of bioactive flavonoids from toothpaste, plant, and saliva. Issue 23 (7th October 2015) - Cao, Wan; Cao, Jun; Ye, Li‐Hong; Xu, Jing‐Jing; Hu, Shuai‐Shuai; Peng, Li‐Qing
Abstract : This article describes the use of the mesoporous molecular sieve KIT‐6 as a sorbent in miniaturized matrix solid‐phase dispersion (MSPD) in combination with ultra‐performance LC for the determination of bioactive flavonoids in toothpaste, Scutellariae Radix, and saliva. In this study, for the first time, KIT‐6 was used as a sorbent material for this mode of extraction. Compared with common silica‐based sorbents (C18 and activated silica gel), the proposed KIT‐6 dispersant with a three‐dimensional cubic Ia3d structure and highly ordered arrays of mesoporous channels exhibits excellent adsorption capability of the tested compounds. In addition, several experimental variables, such as the mass ratio of sample to dispersant, grinding time, and elution solvent, were optimized to maximize the extraction efficiency. The proposed analytical method is simple, fast, and entails low consumption of samples, dispersants and elution solvents, thereby meeting "green chemistry" requirements. Under the optimized conditions, the recoveries of three bioactive flavonoids obtained by analyzing the spiked samples were from 89.22 to 101.17%. Also, the LODs and LOQs for determining the analytes were in the range of 0.02–0.04 μg/mL and 0.07–0.13 μg/mL, respectively. Finally, the miniaturized matrix solid‐phase dispersion method was successfully applied to the analysis of target solutes in real samples, and satisfactory results were obtained.